Safety convention for agricultural workers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A new international convention of labour standards on Health and Safety in Agriculture (see Spore 91) was adopted by an overwhelming majority by the General Conference of the International Labour Organisation in late June.The convention will come...